2016
DOI: 10.1016/j.micres.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacterial and fungal microbiota in sprouts, roots and stems of rice ( Oryza sativa L.)

Abstract: The objective of this study was to elucidate the endophytic microbiota in rice sprouts, roots, and stems, and their transmission in the plant development. Prior to DNA extraction, roots and stems were treated with 36% formaldehyde and 0.1M NaOH solutions to remove epiphytic bacterial whole 16S rRNA genes. Bacterial and fungal taxa in the sprout, root, and stem samples were analyzed using Illumina-based sequencing of the V3-V4 hyper variable regions of bacterial 16S rRNA genes and the ITS2 regions of fungal rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 39 publications
4
53
0
1
Order By: Relevance
“…Evolutionary evidence has suggested that many land plants establish symbiotic relations with diverse microbes, such as bacteria, fungi, and actinomycetes, all of which can dwell in their roots and other organs . Studies have established the beneficial aspects of plant‐microbes in terms of providing a shield against phyto‐pathogens while negating the ill effects of stresses .…”
Section: Mel Regulates Plant‐rhizomicrobial Interactionsmentioning
confidence: 99%
“…Evolutionary evidence has suggested that many land plants establish symbiotic relations with diverse microbes, such as bacteria, fungi, and actinomycetes, all of which can dwell in their roots and other organs . Studies have established the beneficial aspects of plant‐microbes in terms of providing a shield against phyto‐pathogens while negating the ill effects of stresses .…”
Section: Mel Regulates Plant‐rhizomicrobial Interactionsmentioning
confidence: 99%
“…During their evolution, most land plants, developed symbiotic associations with microbes, including fungi, bacteria, and actinomycetes that can grow in the roots and other plant tissues (Compant et al, 2011; Hameed et al, 2015; Wang et al, 2016). Numerous plant-associated microbes are beneficial components of plant micro-ecosystems (Chebotar et al, 2015) because they provide protection against phytopathogens (Lindow and Brandl, 2003; Jetiyanon, 2007), enhance mineral nutrient acquisition (Elbeltagy et al, 2001; Johnson, 2008; Richardson et al, 2009), and help plants withstand abiotic stresses (Castiglioni et al, 2008; Zhang et al, 2008; Khan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, this non-culture method is still not suitable for analyses of the plant endo-bacteriome because of the high sequence identity among bacterial 16S, plant Mt18S and Ct16S sequences. In a few previous studies, bacterial cells have been enriched from plant tissues by washing and vortexing [16,17] or the host DNA has been ltered out from the sequencing results [12,[18][19][20][21]. However, the former approach inevitably leads to an incomplete collection of endophytes, and the latter results in limited sequencing depth and low coverage of bacterial communities.…”
Section: Introductionmentioning
confidence: 99%